Nitric oxide, thyroglobulin, and calcitonin: unraveling the nature of thyroid nodules - Samardzic, Vladimir S.; Macvanin, Mirjana T.; Zafirovic, Sonja S.; Obradovic, Milan M.; Gluvic, Zoran M.; Grubin, Jasmina; Gao, Xin; Essack, Magbubah; Isenovic, Esma R. (Frontiers in Endocrinology, 2023)
Background: Thyroid nodules (TN) are localized morphological changes in the thyroid gland and can be benign or malignant.Objective: The present study investigates the relationships between biochemical markers in serum (s) and their homologs in washout (w) after fine-needle aspiration biopsy (FNAB) of the TN of interest and their correlation with cytology specimen findings.We investigated the relationships between serum biochemical markers nitric oxide (NO), thyroglobulin (TG), and calcitonin (CT), their homologs in washout after FNAB of the TN of interest, and cytology findings of biopsy samples classified according to the Bethesda system for thyroid cytopathology in this study, which included 86 subjects.Results: Washout TG (TGw) level positively correlates with the cytology finding of the biopsy. A higher level of TGw correlates with higher categories of the Bethesda classification and indicates a higher malignant potential. The levels of serum NO (NOs), serum TG (TGs), serum CT (CTs), and washout CT (CTw) do not correlate with the cytology finding of the biopsy, and the higher levels of washout NO (NOw) correspond to the more suspicious ultrasound findings.The findings of our study suggest that TGw and NOw could be used as potential predictors of malignancy in TN.